Sonochemical synthesis and characterization of lead sulfide nanoparticles - Phuruangrata A. (2014)
Large-scale PbS nanoparticles were successfully synthesized by a sonochemical method using Pb(CH 3COO) 2·H 2O and CH 3CSNH 2 as lead and sulfur sources in ethylene glycol as solvent. The structure, morphology and phase of the PbS nanoparticles were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), energy dispersive X-ray (EDX) spectroscopy and photoluminescence (PL) spectroscopy. They were found that the as-synthesized products were cubic structured PbS nanoparticles. By using 254 nm excitation wavelength, the nanoparticles show an emission peak at 390 nm. The formation mechanism of these PbS nanocrystals was also proposed in this report.